Polyamide Backbone Modified Cell Targeting and Penetrating Peptides in Cancer Detection and Treatment - Shah, Sunil S.; Casanova, Nelson; Antuono, Gina; Sabatino, David (Frontiers in Chemistry, 2020)
Cell penetrating and targeting peptides (CPPs and CTPs) encompass an important class of biochemically active peptides owning the capabilities of targeting and translocating within selected cell types. As such, they have been widely used in the delivery of imaging and therapeutic agents for the diagnosis and treatment of various diseases, especially in cancer. Despite their potential utility, first generation CTPs and CPPs based on the native peptide sequences are limited by poor biological and pharmacological properties, thereby restricting their efficacy. Therefore, medicinal chemistry approaches have been designed and developed to construct related peptidomimetics. Of specific interest herein, are the design applications which modify the polyamide backbone of lead CTPs and CPPs. These modifications aim to improve the biochemical characteristics of the native peptide sequence in order to enhance its diagnostic and therapeutic capabilities. This review will focus on a selected set of cell penetrating and targeting peptides and their related peptidomimetics whose polyamide backbone has been modified in order to improve their applications in cancer detection and treatment